The Effect of Learning Approaches and Student Learning Styles on Mathematical Reasoning Abilities - Rivo Panji Yudha (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2019)
This study aims to determine the effect of learning approaches and learning styles on students' mathematical reasoning abilities. This research was a quasi-experimental research with a 2x2 factorial design which was conducted at the Wahidin Vocational School in Cirebom City involving a sample of 70 students from a population of 335 students of class X. Sampling was done by random sampling technique. The research instrument used in the form of tests of mathematical reasoning ability and learning style questionnaire. The collected data were analyzed using the two-way Anava test. Before the two-way anava test is tested, the analysis requirements test is the normality test and the variance homogeneity test. The results of this study are: (1) there is a difference in the effect of the RME learning approach and science on students' mathematical reasoning abilities; (2) There are differences in the influence of kinesthetic learning styles, and visual on students' mathematical reasoning abilities; (3) There is no interaction between learning approaches and learning styles.